COMPARATIVE STUDY OF PSYCHOMOTOR LEVEL BETWEEN SCHOOLCHILDREN FROM PUBLIC AND PRIVATE SCHOOL OF RIO DE JANEIRO (Fiep Bulletin - online, 2016)
The main purpose of this study was to identify and compare the Psychomotor Profile through the Psychomotor Battery-OPB of Vitor da Fonseca (1995) of children from private and public schools of Rio de Janeiro. This research analyzed 400 children, aged 8 and 10 years, from ten schools of Rio de Janeiro, being 40 children in each school, of both genders. Among the 10 schools, 5 were from public schools and 5 private schools. The schools were located in 5 different regions of Rio de Janeiro (Zona Sul, Zona Oeste, Centro, Zona Norte and and Baixada Fluminense) in each region one pubic school and one private school were selected. The instrument used in this study was the Psychomotor Battery of Vitor da Fonseca (1995), which presents an analysis protocol of psychomotor profile by evaluating seven psychomotor factors (Tonicity and Balancing, Lateralization, the Body Concept and Spatial-Temporal Structure, Global praxis and Fine Praxis).The results show that among the groups analyzed, the sample components of the study, private schools have better results on Psychomotor Level in comparison to public schools. The conclusive findings disclosed as a result of this research promotes understanding of the process of motor development of analyzed children when showing differences between the psychomotor structures, which is done as a direct recommendation to the professionals involved with the Basic Education in the sense that they can adapt and qualify the activities proposed in different educational institutions. Public institutions in Brazil, and directly related to this study the ones of Rio de Janeiro require better skills in relation to the work as stimuli to the psychomotor development.
Keywords: Motor Development; Public and Private Education; Psychomotor Level